MANAGEMENT OF THE TEN POWERS SCIENCE PROJECT ACCORDING TO THE FOUR PRINCIPLES OF IDDHIPADA OF BANTUADTHONG SCHOOL NETWORK UNDER THE NAKHON SI THAMMARAT EDUCATIONAL SERVICE AREA OFFICE 1 - Kaewkao, Sunattra; PhrakhruPrachotkitchaphon; Weeraponkan, Boonlert (Journal of Educational Review Faculty of Education in MCU, 2025)
This research article aimed to: 1) study the conditions of the Ten Powers Science Project of Ban Thuat Thong School Center Network, 2) Study the management guidelines for the Ten Powers Science Project according to the principles of Four Iddhipda of the Ban Thuat Thong School Center Network, 3) Present and evaluate the management guidelines of Ten Powers Science Project according to the principles of Four Iddhipda of the Ban Thuat Thong School Center network under the Nakhon Si Thammarat Primary Educational Service Area Office 1. This study employs a qualitative research methodology. The investigation of the current management conditions was conducted through in-depth interviews with 20 relevant stakeholders. The study of management approaches involved in-depth interviews with 10 key informants. Lastly, the proposal and evaluation of management approaches were carried out through a focus group discussion with seven experts. Data were analyzed using inductive analysis. The results of the research found that: 1) Current management conditions: The schools lacked sufficient learning resources to support students effectively. Additionally, students had varying educational backgrounds and interests, leading to a lack of motivation to apply scientific knowledge in daily life. However, teachers strived to create an environment that encourages analytical thinking and problem-solving through continuous curriculum monitoring and assessment. 2) Guidelines for managing the Ten Powers Science Project according to the Four Iddhipda principles. It was found that the process of implementing the Ten Powers Science Project had the Four Iddhipda principles applied in every step of all 3 standards. 3) Evaluation of the proposed management approaches: Experts participating in the focus group discussion reached a unanimous agreement that the proposed management approaches were appropriate, feasible, and beneficial.